Towards the semantic differentiation problem of epistolary text denotations in Ancient Russian and Old Russian written monuments: Greecisms грамота, епистолия, хартия, харатия - Zuyeva, Volha U. (Journal of the Belarusian State University. Philology, 2023)
The purpose of the study is to establish the differences in meaning between the lexical and semantic variants of the words грамота, епистолия, хартия, харатия, which are united by the common meaning ‘epistolary text’, in the Ancient Russian language and in the Old Russian language. For the analysis of semantics, the most ancient Greek borrowings were selected, as well as the nominations грамотица and грамотка derived from грамота. The designations, except for the words хартия, харатия, are not absolute synonyms at different historical periods. In the Ancient Russian language, these Greek borrowings were polysemantic, in particular, they could designate both an epistolary text and an official document, which is one of the factors that determine the problem of distinguishing act sources and epistolary sources. For the lexeme грамота in the Old Russian period too, the designation of both types of the sources was equally relevant, this word was not limited to the framework so-called book culture and the only one of those analysed became the basis for the formation of other genre designations. The lexeme грамота and the derivative word грамотка were not used to designate private spiritual messages, in contrast to the nominations хартия and епистолия. The Greek borrowing епистолия, which had notable literary stylistic features throughout the selected period, revealed the widest semantic range, while in the Old Russian language this word practically completely lost the meaning of ‘document’. The epistolary meaning of the lexeme хартия in the Old Russian language goes into passive linguistic knowledge, on the contrary. All the analysed words could be used in narrative texts in relation to a form of letters not specified in content, that is, when denotating the situation of the epistolary dialogue in general.